Model Penentu Pencapaian Pelajar Untuk Program Kerjasama UUM-IPTS - Noorezatty, Mohd. Yusop (2003)
The aim of this study is to determine whether or not the students’ performance of BBA (Hons) collaborative programme between UUM-IPTS depends on the results of entry qualifications and demographic factors. The final cumulative grade point average (CGPA) obtained by these students at the end of their studies are considered as indicator of their academic performance. The population of this study is 189 students and 130 of them are taken as a sample. Logistic Regression and Multinomial Regression Analysis with Chi-square and t-test are applied on the factors in order to develop three models. The results shows that the students’ performance in Mathematics at SPM level, the type of entry qualifications (STPM or Diploma) as well as ethnic contribute to the students’ performance. The developed models can be used as a guideline for student intake for collaborative programme.